Towards drone-based magnetometer measurements for archaeological prospection in challenging terrain - Schmidt, Volkmar; Coolen, Joris; Fritsch, Thomas; Klingen, Stefan (Drone systems and applications, 2024)
While airborne magnetometry has been used for geological surveys for decades, magnetic surveys for archaeological prospection are almost exclusively ground-based, as the detection of archaeological features requires higher spatial resolution and close proximity between sensor and object. However, the recent development of drones and magnetic sensors allows for low-altitude drone-based surveys, which are an interesting alternative for magnetic prospection of challenging areas, where vegetation, difficult terrain, access restrictions, or safety concerns hamper ground-based surveys. In this paper, we present test measurements in challenging areas in Germany and Switzerland, which demonstrate the potential as well as technical and practical concerns of drone-based magnetometry for archaeological prospection. We used a miniature total-field magnetometer, which was tethered to an octocopter drone. Although it is preferable to fly the sensor close to the ground where anomalies show the highest values, we could also detect magnetic anomalies in altitudes up to few metres above ground. Flights at different altitudes show the decay and widening of the anomalies with height. Drone-based magnetic measurements in rough and vegetated terrain require careful flight planning based on a high-resolution surface model. Further development is needed to improve positioning accuracy of the tethered magnetometer and to improve heading error correction.